Neuroinflammation in suicide: Toward a comprehensive model. (16th November 2016) - Courtet, Philippe; Giner, Lucas; Seneque, Maude; Guillaume, Sebastien; Olie, Emilie; Ducasse, Deborah
Abstract : Objectives. Suicidal behaviour (SB) entered the DSM-5, underlying a specific biological vulnerability. Then, recent findings suggested a possible role of the immune system in SB pathogenesis. The objective of this review is to present these main immune factors involved in SB pathogenesis. Methods. We conducted a review using Preferred Reporting Items for Systematic reviews and Meta-Analysis criteria, and combined ("Inflammation") AND ("Suicidal ideation" OR "Suicidal attempt" OR "suicide"). Results. Post mortem studies demonstrated associations between suicide and inflammatory cytokines in the orbitofrontal cortex, a brain region involved in suicidal vulnerability. Also, microgliosis and monocyte–macrophage system activation may be a useful marker of suicide neurobiology. Kynurenine may influence inflammatory processes, and related molecular pathways may be involved in SB pathophysiology. Few recent studies associated inflammatory markers with suicidal vulnerability: serotonin dysfunction, impulsivity and childhood trauma. Interestingly, the perception of threat that leads suicidal individuals to contemplate suicide may activate biological stress responses, including inflammatory responses. Conclusions. Translational projects would be crucial to identify a specific marker in SB disorders, to investigate its clinical correlations, and the interaction between inflammatory cytokines and monoamine systems in SB. These researches might lead to new biomarkers and novel directions for therapeutic strategies.